Ukrainian secondary school students about distance education = Ukraińcy uczniowie szkół średnich o kształceniu na odległość - Borysov, Roman (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article addresses the issue of the implementation of distance education in the final year of secondary school. The author pays special attention to the attitude of secondary school students, who are a key subject of the educational process, to the introduction of distance education. The empirical basis of the study includes the results of a study carried out among the students of the 11th grades in Kharkiv, Odesa, Cherkasy and Ivano-Frankivsk, which was conducted 1.5 years after the introduction of online education. Key problems associated with the introduction of distance education were identified: the rejection of distance learning as a format suitable for basic education, and the lack of sufficient communication with teachers and classmates. Such problems lead to the perception of this mode as anomalous, forced and temporary.
Keywords: distance education; secondary school; students; COVID-19; kształcenie na odległość; szkolnictwo ponadpodstawowe; uczniowie